Pengembangan E-modul berbasis Multiple Representation untuk Meningkatkan Kompetensi Literasi Kimia dan Kemandirian Belajar Siswa pada Materi Laju Reaksi - Dini Adelia; Roza Linda; Maria Erna (Postgraduate, University of Mataram, 2023)
In The learning process, learning media, students, educators, environment conditions and everything related to education have a reciprocal relationship that is mutually dependent on each other and mutually utilizes each other with the aim of forming character in students who think cognitively and independently. The aim of this research is to determine the level of validity and practice of e-modules based on multiple representations to increase chemical literacy in odd semester class XI high school chemistry material in accordance with the independent learning curriculum. This type of research is R&D (Presearch & Development). Where this research produces products and tests the effectiveness of the products produced. Data collection techniques were carried out through interviews, validity sheets, teacher practitioner questionnaires and student response tests. The research results found that the E-module product based on multiple representations of reaction rate subject matter was very valid in terms of material validation, media validation and practitioners by teachers in the field of chemistry studies. So, it can be used in the learning process. Thus, the product developed can help teachers convey reaction rate material in an independent curriculum.